Clinical, Economic, and Humanistic Outcomes Associated with Obesity Among People with Bipolar I Disorder in the United States: Analysis of National Health and Wellness Survey Data - Doane MJ; Thompson J; Jauregui A; Gasper S; Csoboth C (Dove Medical Press, 2023)
Michael J Doane,1 Jeffrey Thompson,2 Adam Jauregui,2 Sabina Gasper,1 Csilla Csoboth1 1Alkermes, Inc., Waltham, MA, USA; 2Cerner Enviza, North Kansas City, MO, USACorrespondence: Michael J Doane, Health Economics and Outcomes Research, Alkermes, Inc, 825 Winter Street, Waltham, MA, 02451-1420, USA, Tel +1-781-290-7183, Email michael.doane@alkermes.comIntroduction: People living with bipolar I disorder (BD-I) have an increased risk for obesity compared with the general population that may be related to genetic, lifestyle, and treatment factors. Few studies have examined possible effects of obesity on those living with BD-I. This study examined relationships between obesity and clinical, humanistic, and economic outcomes among adults with BD-I.Methods: This retrospective, cross-sectional study analyzed survey responses from a nationally representative sample of US adults participating in the 2016 or 2020 National Health and Wellness Survey. Respondents (18- 64 years) with a self-reported physician diagnosis of BD-I were included and categorized by body mass index: underweight/normal weight (< 25 kg/m2), overweight (25 to < 30 kg/m2), or obese (≥ 30 kg/m2). Adjusted analyses assessed comorbidities, health-related quality of life (HRQoL), work productivity, health care resource utilization (HCRU), and economic outcomes.Results: In total, responses from 1,853 participants were analyzed; most were female (65%) and white (62%). Respondents with obesity had the highest prevalence of medical comorbidities, including high blood pressure (52%), sleep apnea (37%), hypercholesterolemia (34%), and type 2 diabetes (12%). Obesity was generally associated with the lowest scores of physical health and HRQoL. Activity impairment scores were highest among respondents with obesity, as were numbers of hospitalizations and emergency department visits in the previous 6 months. Respondents with obesity incurred higher annual indirect and direct medical costs ($28,178 and $37,771, respectively) when compared with the underweight/normal weight ($23,823 and $32,227, respectively) and overweight ($24,312 and $35,231, respectively) groups.Conclusion: In this nationally representative sample, obesity was associated with several outcomes that may negatively affect people living with BD-I, including medical comorbidities, higher HCRU, HRQoL impairments, and greater indirect and direct medical costs. These findings highlight the importance of considering the presence of or risk for obesity and associated medical comorbidities when treating BD-I.Keywords: body mass index, comorbidity, health care costs, health-related quality of life